The Early Warning System in Preventing Human Trafficking: Border (In) Security and Challenges for Indonesia - Azizurrahman, Sy. Hasyim; Ismawati, Sri; Siagian, Parulian; Had, Abunawas; Tahir, Muhammad; Alkadri, Sy. Muhammad Ridho Rizki Maulufi (Faculty of Law, Hasanuddin University, 2023)
This article aims to find out how the early warning system is constructed in detecting human trafficking. This research discusses human trafficking in Indonesia, where most of the victims were trafficked to neighboring countries in the border area. One of the unsolved problem exist today is human trafficking in frontier areas; hence, there are three major factors causing the number of human trafficking in Indonesia is in high level according to data from the International Organization for Migration. This article is using empirical legal research method. The results show that the construction of an early warning system can be formed by studying the methods or modes used by the perpetrators in committing the crime of human trafficking. However, for this concept to succeed, good synchronization is needed between filters that include potential victims, agencies or institutions that can represent administrative functions, and officers at border area guard posts.